Preparation and Characterization of Curcumin Loaded Dextrin Sulfate- Chitosan Nanoparticles for Promoting Curcumin Anticancer Activity: Physicochemical properties of polymeric nanoparticles- curcumin - Elbialy, Nihal S (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Curcumin as a natural medicinal agent has been proved to kill cancer cells effectively. However, its biomedical applications have been hindered owing to its poor bioavailability. Many nanoparticulate systems have been introduced to overcome this problem. Among this types polymeric-based nanoparticles which exhibit unique properties allowing their use as a efficient drug carrier. Developing a polymeric- blend nanoparticles will offer a promising nanocarrier with excellent biocompatibility, biodegradability and low immunogencity. In this study, curcumin nano-vehicle has been made up by combining dextren sulfate and chitosan (DSCSNPs). DSCSNPs have been characterized using different techniques. Transmission electron microscopy (TEM) which revealed the spherical, smooth surface of the nano-formulation. Dynamic light scattering (DLS) for measuring DSCSNPs hydrodynamic- diameter. Zeta potential measurements showed nanoparticles high stability. Fourier transform infrared spectroscopy (FTIR) confirmed successful combination between the two polymers and curcumin loading on naoparticles surface. Curcumin release profile out of DSCSNPs showed high drug release in tumor acidic microenvironment. In vitro cytotoxicity measurements demonstrated that curcumin loaded polymeric nanoparticles (DSCSNPs-Cur) have high therapeutic efficacy against colon (HCT-116) and breast (MCF-7) cancer cells compared with free curcumin. DSCSNPs as a combined biopolymers is an excellent candidate for improving curcumin bioavailability allowing its use as anticancer agent.